Chronic glucocorticoid exposure accelerates Aβ generation and neurotoxicity by activating calcium-mediated CN-NFAT1 signaling in hippocampal neurons in APP/PS1 mice. (October 2022) - Ding, Shixin; Yang, Liu; Huang, Lei; Kong, Liangliang; Chen, Ming; Su, Yong; Li, Xuewang; Dong, Xianan; Han, Yuli; Li, Weiping; Li, Weizu
Abstract: Glucocorticoid (GC) exposure can lead to deterioration of the structure and function of hippocampal neurons and is closely involved in Alzheimer's disease (AD). Amyloid-β (Aβ) overproduction is an important aspect of AD pathogenesis. Our study mainly investigated the mechanism of chronic GC exposure in accelerating Aβ production in primary cultured hippocampal neurons from APP/PS1 mice. The results indicated that chronic dexamethasone (DEX, 1 μM) significantly accelerated neuronal damage and Aβ accumulation in hippocampal neurons from APP/PS1 mice. Meanwhile, DEX exposure markedly upregulated APP, NCSTN, BACE1 and p-Tau/Tau expression in hippocampal neurons from APP/PS1 mice. Our study also indicated that chronic DEX exposure significantly increased intracellular Ca 2+ ([Ca 2+ ]i ) levels and the expressions of p-PLC, CN and NFAT1 in hippocampal neurons from APP/PS1 mice. We further found that stabilizing intracellular calcium homeostasis with 2-APB (50 μM) and SKF-96365 (10 μM) significantly alleviated neuronal damage and Aβ accumulation in chronic DEX-induced hippocampal neurons from APP/PS1 mice. Additionally, dual luciferase assays showed that NFAT1 upregulated NCSTN transactivation, which was further increased upon DEX treatment. This study suggests that chronic DEX exposure accelerates Aβ accumulation by activating calcium-mediated CN-NFAT1 signaling in hippocampal neurons from APP/PS1 mice, which may be closely related to the acceleration of AD. Graphical abstract: Image 1 Highlights: Chronic DEX promotes Aβ accumulation and neurotoxicity in hippocampal neurons of APP/PS1 mice. Chronic DEX induces PLC activation and Ca 2+ overload in hippocampal neurons of APP/PS1 mice. Chronic DEX activates CN-NFAT1 signaling in hippocampal neurons of APP/PS1 mice. Stabilizing calcium homeostasis alleviates chronic DEX-induced Aβ generation and neurotoxicity.